Increased Incidence of Colon Tumors in AOM-Treated Apc1638N/+ Mice Reveals Higher Frequency of Tumor Associated Neutrophils in Colon Than Small Intestine - Metzger, Rebecca; Maruskova, Mahulena; Krebs, Sabrina; Janssen, Klaus-Peter; Krug, Anne B. (Frontiers in Oncology, 2019)
Colorectal cancer (CRC) is one of the most common cancers and a major cause of mortality. Mice with truncating Apc germline mutations have been used as a standard model of CRC, but most of the Apc-mutated lines develop multiple tumors in the proximal small intestine and rarely in the colon precluding detailed analysis of colon tumor microenvironment. Our aim was to develop a model with higher resemblance to human CRC and to characterize tumor infiltrating immune cells in spontaneously developing colon tumors compared to small intestinal tumors. Therefore, the Apc1638N/+ line was treated repeatedly with the azoxymethane (AOM) and 90% colon tumor incidence and 4 to 5 colon tumors per mouse were achieved. Of note, AOM treatment specifically increased the tumor burden in the colon, but not in the small intestine. Histological grading and WNT-signaling activity did not differ significantly between small intestinal and colon tumors with some lesions progressing to invasive adenocarcinoma in both locations. However, characterization of the intratumoral myeloid cell compartment revealed a massive infiltration of colon tumors with neutrophils - 6-fold higher than in small intestinal tumors. Moreover, CCL17-expressing macrophages and dendritic cells accumulated in the tumors indicating the establishment of a tumor-promoting immunosuppressive environment. Thus, Apc1638N/+ mice treated with AOM are a suitable and straighforward model to study the influence of immune cells and chemokines on colon carcinogenesis.